ANALISIS DAMPAK SERVICE PERFORMANCE DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS DI RESTO AYAM GORENG NELONGSO CABANG BENDUNGAN SUTAMI MALANG) - Fifit Nurta Syaifudin; Rois Arifin (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study uses quantitative data collection through questionnaires. The population in this study is Consumer Resto Fried Chicken Nelongso Branch Sutami Dam Malang. The sample took 88 respondents with data collection techniques using a questionnaire. The objectives of this study are: 1) Effect of Service Performance and Satisfaction on consumer loyalty at Resto Ayam Goreng Nelongso Sutami Branch. 2) Partial Performance Analysis of Service Performance and Satisfaction with Customer Loyalty at Resto Ayam Goreng Nelongso Sutami Branch.               The results showed that: 1) Can show simultaneous performance of services and satisfaction with customer loyalty at Nelongso fried chicken restaurant. 2) Related to the partial performance between service performance and satisfaction with customer loyalty at Nelongso fried chicken restaurant. Keywords: Service performance, Authority, Customer Loyalty